Portrait of the Arabic Literature Existence in East Asia - Tafuzi Mu’iz, Dzikrul Hakim; Zuhdy, Halimi; Bahruddin, Uril; Yujia, Jin (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2023)
Arabic literature in the East Asian region shows the existence of a cultural diaspora that has been going on for centuries. Internal factors of population dispersal can be guessed by the discomfort of living in the place of origin due to prolonged conflicts that require Arabs to migrate. East Asia is an exciting option to highlight because it has long-standing bilateral relations with the Arabian Peninsula region. This research uses qualitative methods with Robin Cohen's transnational diaspora approach to understand the existence of Arabic literature in East Asia. Data was collected by reading articles and documenting matters highlighting Arabic literature's presence in East Asia. This study found that Arabic literature has existed in East Asia since Islam. This existence is related to bilateral relations between business sector areas, student exchanges, peace agreements, and political marriages. يظهر الأدب العربي في منطقة شرق آسيا وجود شتات ثقافي مستمر منذ قرون. يمكن تخمين العوامل الداخلية للتشتت السكاني من خلال عدم الراحة من العيش في مكان المنشأ بسبب النزاعات المطولة التي تتطلب هجرة العرب. تعد منطقة شرق آسيا خيارا مثيرا يجب تسليط الضوء عليه لأن لديها علاقات ثنائية طويلة الأمد مع منطقة شبه الجزيرة العربية. يستخدم هذا البحث أساليب نوعية مع نهج روبن كوهين للشتات العابر للحدود لفهم وجود الأدب العربي في منطقة شرق آسيا. تم جمع البيانات من خلال قراءة المقالات وتوثيق الأمور التي تسلط الضوء على وجود الأدب العربي في منطقة شرق آسيا. وجدت هذه الدراسة أن الأدب العربي موجود في شرق آسيا منذ الإسلام. يرتبط هذا الوجود بالعلاقات الثنائية التي تتم بين المناطق في قطاع الأعمال، وتبادل الطلاب، واتفاقيات السلام، والزواج السياسي.